Software Requirement Analysis: Research Challenges and Technical Approaches - Demirel, Senay Tuna; Das, Resul (Ieee, 2018)
Requirement analysis is one of the key challenges in software development projects. Customer requirement specification and management entails various impacts to software projects and still is an improvement area on both academic and industrial fields. Models like CMMI also uncovers requirement development and management and specifies the specific goals and practices for them. In this paper, key challenges and issues of requirement management are listed with respect to a standardization activity, namely CMMI.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Requirement Analysis and Management; Software Delivery Life Cycle (SDLC); Agile; Waterfall; Capability Maturity Model Integration (CMMI)